(untitled) (LIS TODAY, 2025)
The library assumes an extremely indispensable part in the advanced education framework by giving pertinent data and information to the academic local area and is treated as the core of the scholarly framework. The changing in the data climate, and the use of the ICT framework in libraries have made both library experts and users befuddled to find suitable data as and when required. The investigation of the utilization of library services and users’ fulfillment extraordinarily affects future library administrations by updating the library assortment advancement strategy and administrations in view of users’ perspectives and requests and for this assessment of user fulfillment with library assets and administration is important to give information sources and services to meet user’s data prerequisites however no review is being done work today to know the utilization of library assets and client fulfillment on libraries’ resources and services in NAAC Accredited, Government Aided General Degree College Libraries in Bankura.